2004
DOI: 10.1093/molbev/msi061
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Evolution and Functional Diversification of Type-III Secretion Systems in the Insect Endosymbiont Sodalis glossinidius

Abstract: Sodalis glossinidius, a maternally transmitted endosymbiont of tsetse flies, maintains two phylogenetically distinct type-III secretion systems encoded by chromosomal symbiosis regions designated SSR-1 and SSR-2. Although both symbiosis regions are closely related to extant pathogenicity islands with similar gene inventories, SSR-2 has undergone novel degenerative adaptations in the transition to mutualism. Notably, SSR-2 lacks homologs of genes found in SSR-1 that encode secreted effector proteins known to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…TTSS have been shown to deliver effector proteins that mediate host cell invasion in S. enterica (45) and many other animal and plant pathogens (46,47), and in some insect symbionts (15)(16)(17). Haghjoo and Galan (48) discerned a link between the TTSS and CdtB in S. enterica sv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTSS have been shown to deliver effector proteins that mediate host cell invasion in S. enterica (45) and many other animal and plant pathogens (46,47), and in some insect symbionts (15)(16)(17). Haghjoo and Galan (48) discerned a link between the TTSS and CdtB in S. enterica sv.…”
Section: Discussionmentioning
confidence: 99%
“…13 and 14). In the tsetse fly symbiont, Sodalis glossinidius, for example, two type III secretion systems (TTSS) are present, and at least one is required for invasion of host cells (15,16), as is true of many pathogens, including S. enterica and Y. pestis. A TTSS also appears to underlie infection of host cells by the symbionts of Sitophilus weevils (17) and by Photorhabdus species infecting nematodes (18).…”
mentioning
confidence: 99%
“…The TTSS gene cluster is often referred as a "pathogenicity island", because many pathogens use this secretion system to inject their effector proteins into eukaryotic host cells, which induce endocytosis and/or apoptosis in the host cells (7,40). Further studies have revealed that Sodalis employs the TTSS to invade host cells both in vitro and in vivo (28,31), providing the first insight into the molecular mechanisms essential for establishing and maintaining insect endosymbiosis. More importantly, these results clearly demonstrated that all microbes, regardless of association types, utilize similar molecular mechanisms for interacting with their host organisms.…”
Section: Special Issuementioning
confidence: 99%
“…As shown in the Sodalis-tsetse symbiosis (28,31), model systems with culturable symbionts offer new revelations regarding microbial endosymbiosis, providing us with an opportunity to investigate these symbiotic associations using powerful experimental tools like genetic manipulation. Other model systems with culturable symbionts, including legume-Rhizobium and squid-Vibrio symbioses, have enriched our knowledge of the molecular mechanisms behind host-symbiont interactions, though there have been few comparative studies because of the lack or limited diversity of symbiotic association within each specific taxonomic group.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Once established within the host, endosymbionts generally experience severe genome size reduction due to relaxed evolutionary pressures on genes that are redundant with host functions [17][18][19] or become unnecessary for the new association [20]. Among the latter, virulence genes and genes involved in the biosynthesis of cell wall components, are prone to deletion [20][21][22]. As these elements constitute microbe-associated molecular patterns (MAMPs) that are central for bacterial perception by insect immune pattern recognition receptors (PRRs), the molecular cross-talk used by partners to 'manage' their coexistence may vary according to the age of the association, and hence to the level of bacterial genome reduction.…”
Section: Introductionmentioning
confidence: 99%